Synthesis and characterization of sodium, potassium, zinc and aluminium formamidinate complexes. Issue 1 (13th January 2021) - Salehisaki, Mehdi; Rad, Nazli E.; Junk, Peter C.; Deacon, Glen B.; Wang, Jun
Abstract: The metalation reactions of N, N' -bis-(2, 4-dimethylphenyl)formamidine (DMFormH) and N, N'-bis-(phenyl)formamidine (PhFormH) with KN(SiMe3 )2 or NaN(SiMe3 )2 in toluene/1, 2-dimethoxyethane (dme) resulted in the formation of [K(DMForm)(dme)]n (K1 ), [K2 (PhForm)(N(SiMe3 )2 )]n (K2 ), [Na(DMForm)(dme)2 ] (Na1 ), and [Na(PhForm)(dme)]2 (Na2 ). Treatment of PhFormH with ZnEt2 or AlMe3 in toluene/tetrahydrofuran (thf) yielded [Zn4 (PhForm)6 O]·2.5thf (Zn1 ) and [Al(PhForm)3 ] (Al1 ), respectively. The potassium-formamidinate compounds (K1 and K2 ) are polymeric. K1 has six-coordinate potassium with additional C…K interactions. Reducing the steric effect of the formamidinate changes the formamidinate bonding mode. Thus, for potassium complexes, it led to both inter- and intra-molecular η 6 -arene-K binding in K2 . With the sodium complexes, the structure changed from a six-coordinate monomer in [Na(DMForm)(dme)2 ] to a five-coordinate dimer in [Na(PhForm)(dme)]2 in which there is a μ 2 -1 κ ( N, N' ): 2 κ ( N ) formamidinate binding mode. Zn1 has a pseudo-cubane oxide centered cage like structure, whereas Al1 is monomeric with six-coordinate aluminium and chelating formamidinate ligands. Graphical Abstract: